2021
DOI: 10.3390/cancers13205190
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Diacylglycerol Kinase α in Cancer Cell Proliferation and Apoptosis

Abstract: Diacylglycerol (DG) kinase (DGK) phosphorylates DG to generate phosphatidic acid (PA). The α isozyme is activated by Ca2+ through its EF-hand motifs and tyrosine phosphorylation. DGKα is highly expressed in several refractory cancer cells including melanoma, hepatocellular carcinoma, and glioblastoma cells. In melanoma cells, DGKα is an antiapoptotic factor that activates nuclear factor-κB (NF-κB) through the atypical protein kinase C (PKC) ζ-mediated phosphorylation of NF-κB. DGKα acts as an enhancer of proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…Our findings raise many questions that remain to be investigated, such as whether DGKα activity is elevated in Ras-driven polarity-impaired cells and, if so, how this occurs, and whether increased PA-signalling or decreased DAG signalling provide the critical function of DGKα in tumourigenesis. However, since DGKα is upregulated and oncogenic in human cancer (Chen et al, 2019;Fazio et al, 2020;Merida et al, 2017;Sakane et al, 2021), the findings from our study suggest that Rasdriven polarity-impaired cancers may be particularly addicted to DGKα for tumour survival, and suggests that DGKα-inhibitors combined with Ras pathway inhibitors will be a highly effective drug combination for anti-cancer therapy in these cancers. DGKα inhibitors have been considered for development as anti-cancer therapy not only for their effect on the cancer but also on the T-cell anti-cancer immune response (Arranz-Nicolas and Merida, 2020;Sakane et al, 2008;Sakane et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Our findings raise many questions that remain to be investigated, such as whether DGKα activity is elevated in Ras-driven polarity-impaired cells and, if so, how this occurs, and whether increased PA-signalling or decreased DAG signalling provide the critical function of DGKα in tumourigenesis. However, since DGKα is upregulated and oncogenic in human cancer (Chen et al, 2019;Fazio et al, 2020;Merida et al, 2017;Sakane et al, 2021), the findings from our study suggest that Rasdriven polarity-impaired cancers may be particularly addicted to DGKα for tumour survival, and suggests that DGKα-inhibitors combined with Ras pathway inhibitors will be a highly effective drug combination for anti-cancer therapy in these cancers. DGKα inhibitors have been considered for development as anti-cancer therapy not only for their effect on the cancer but also on the T-cell anti-cancer immune response (Arranz-Nicolas and Merida, 2020;Sakane et al, 2008;Sakane et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…DGK α is considered an oncogene, being upregulated in many cancers, and promotes cell proliferation and cell survival (Chen et al, 2019; Fazio et al, 2020; Merida et al, 2017; Sakane et al, 2021). Mechanistically, we showed that inhibition of DGK α in human mammary epithelial cells harbouring the H-RAS oncogene and knockdown of the cell polarity gene, SCRIB , resulted in reduced MEK and mTOR activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a human trial observed protection against podocyte apoptosis by green tea polyphenols in DN [ 89 ]. In cancer cells, it is well known that DGKα prevents apoptosis via various signaling pathways, followed by PA production [ 104 , 105 , 106 ], suggesting the involvement of DGKα in the prevention of apoptosis of podocytes by green tea polyphenols, especially EGCG. Taken together, DGKα activation ameliorates DN by not only inhibiting PKCs by reducing the amount of DG but also by generating PA activating downstream signaling pathways.…”
Section: The Mechanisms Of the Amelioration Of Dn By Dgkα Activationmentioning
confidence: 99%